2011
DOI: 10.1111/j.1751-5823.2011.00148.x
|View full text |Cite
|
Sign up to set email alerts
|

Autocorrelation Functions

Abstract: SummaryWe explain the connection between autocorrelation functions of stationary continuous time processes and real characteristic functions, and review sufficient conditions for a function to be an autocorrelation function. We also give probabilistic constructions for time series reformulations of Pólya's (1949) Theorem on characteristic functions, and Young's (1913) classical theorem in Fourier analysis. Our constructions allow the marginal distribution of the process to be any infinitely divisible distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…A nice review of several versions of Pólya‐type functions can be found in Finlay et al . (). As Chung () and Finlay et al .…”
Section: Construction Of Stationary Process With Pólya‐type Covariancmentioning
confidence: 97%
See 4 more Smart Citations
“…A nice review of several versions of Pólya‐type functions can be found in Finlay et al . (). As Chung () and Finlay et al .…”
Section: Construction Of Stationary Process With Pólya‐type Covariancmentioning
confidence: 97%
“…As Chung () and Finlay et al . () pointed out, the condition limxg(x)=0 in a Pólya‐type function may be substituted by limxg(x)=a00. Theorem can be modified appropriately to cover this case as well.…”
Section: Construction Of Stationary Process With Pólya‐type Covariancmentioning
confidence: 99%
See 3 more Smart Citations